Factores de riesgos mecánicos y eléctricos que inciden en la seguridad y salud de los estudiantes que utilizan los talleres de Electricidad y Mecánica Automotriz del colegio Nacional Técnico Industrial Juan Abel Echeverría durante el período académico 2010 - 2011. Propuesta de un manual de seguridad en prevención de riesgos mecánicos y eléctricos. - Remacha Valverde, Luis Gonzalo (2012)
The present research is the effect of the implementation of the occupational Safety and Health attention to a major issue that handles the change with emphasis on identification and risk assessment for the improvement of operational activities in de workshops of the technical area in the Juan Abel Echeverría National Industrial Technical High School of Latacunga. The research is based on an analysis of documents from other subjects with similar characteristics to the Safety and Occupational Health in order to determine the best option to apply them in this case. It is supported with scientific content about electrical and mechanical risk factors, students and teachers of the technical area of the National Industrial Technical Juan Abel Echeverría High School are surveyed, the results are analyzed to define the problem by itself and so, conclude and recommend an appropriately focused proposal to achieve a Security Manual to be successful, that achieves the objectives set by the policy of the Institution, this manual has to be realistic, communicative, which has the support of the authorities, with the necessary technical and human resources and what is more with the collaboration and commitment of all involved in the workshops of the technical area. In the proposed Safety Manual is necessary to mention the proper use of equipment and hand tools as well as its preserving orderly and organized, actions that will tend to improve continuously the activities in a safe manner, the same as will promote an interest in security and Occupational Health of all those working in the National Industrial Technical Juan Abel Echeverria High School. The methodology which was used is within the requirements of a feasible project, as well as those established by the scientific research.